2003
DOI: 10.1111/j.1439-0272.2003.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

The limit of leucocytospermia from the microbiological viewpoint

Abstract: The aim of the study was to find out the correlation between white blood cell (WBC) counts in semen and quantitative composition of seminal microflora, and to establish the minimum WBC count associated with significant bacteriospermia. The research included 159 men with different WBC counts in their semen, 84 of them with chronic prostatitis/chronic pelvic pain syndrome. Semen samples were cultivated quantitatively for detecting anaerobic, microaerophilic and aerobic bacteria. Bryan-Leishman stained slides wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…However, some authors have postulated the necessity to reevaluate this threshold [47][48][49][50]. According to the kinetics of the inflammatory process in the urogenital tract previously proposed by our group, leukocytes appear in semen as the addition to bacteriospermia at the second stage of the urogenital tract infection, and remain present in semen for some length of time following the elimination of the bacteria in the third stage (isolated leukocytospermia) [51].…”
Section: Coli Staphylococcus (S) Aureus Enterococcus (E) Faecalismentioning
confidence: 99%
“…However, some authors have postulated the necessity to reevaluate this threshold [47][48][49][50]. According to the kinetics of the inflammatory process in the urogenital tract previously proposed by our group, leukocytes appear in semen as the addition to bacteriospermia at the second stage of the urogenital tract infection, and remain present in semen for some length of time following the elimination of the bacteria in the third stage (isolated leukocytospermia) [51].…”
Section: Coli Staphylococcus (S) Aureus Enterococcus (E) Faecalismentioning
confidence: 99%
“…Most studies show no correlation between the presence of leukocytes and bacteria in semen [74][75][76]. However, Punab et al observed a positive correlation between the leukocyte count and the number of different bacteria detected in semen, and also between the leukocyte count and the total count of microorganisms in semen samples [77]. In fact, these authors along with Gdoura et al [78] demonstrated that the WHO-defined cut-off point (1x10 6 leukocytes per mL) has very low sensitivity for discriminating between patients with and without significant bacteriospermia, as a more optimal sensitivity/specificity ratio appears at 0.2x10 6 leukocytes per mL of semen.…”
Section: The Controversial Role Of Leukocytospermia On Fertilitymentioning
confidence: 99%
“…Some have found this value too low [1], others too high [2,3], depending on the end-point examined (semen quality, In Vitro Fertilization [IVF] results, bacterial presence, sperm response to reactive oxygen species). Other values from 0.5 × 10 6 -1.0 × 10 6 polymorphs per mL or 1 × 10 6 -2 × 10 6 leukocytes per mL have been suggested [1].…”
Section: Introductionmentioning
confidence: 99%
“…Wolff et al [5] diluted semen 1 + 1 with reagent, which should present 50 cells (%SE 14%) in the central Neubauer grid, providing estimates of 1 280 000 to 720 000 cells per mL. Punab et al [3] assessed the leukocyte concentration by comparing their number per microscope field relative to those of spermatozoa and multiplying by the sperm concentration. As a total of 200 round cells was counted, which gives a %SE of 7%, a true value of 10 6 mL -1 could be assessed as 1 140 000 or 860 000 cells per mL, although the accuracy of the method of assessing sperm concentration was not given.…”
Section: Introductionmentioning
confidence: 99%